2005
DOI: 10.1530/eje.1.02027
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous adipocytes from obese hyperinsulinemic women with polycystic ovary syndrome exhibit normal insulin sensitivity but reduced maximal insulin responsiveness

Abstract: Background: Polycystic ovary syndrome (PCOS) has a high prevalence in women and is often associated with insulin resistance and hence with aspects of the so-called metabolic syndrome. Methods: Ten women diagnosed with PCOS were consecutively included (aged 21-39 years, average 30.2^1.9 years; body mass index 28.4 -42.5 kg/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…Rosenbaum et al reported a decrease in maximal insulin-stimulated glucose transport in adipocytes of women with PCOS [20], a defect that was not, however, confirmed by Ciaraldi et al [13]. Moreover, Lystedt et al found a normal insulin dose-response curve along with diminished maximal insulin-stimulated glucose transport in subcutaneous adipocytes of obese PCOS women [21]. Ciaraldi et al also showed decreased maximal insulin-stimulated autophosphorylation with no apparent defect in receptor kinase activity [13].…”
Section: Peripheral Tissuesmentioning
confidence: 98%
“…Rosenbaum et al reported a decrease in maximal insulin-stimulated glucose transport in adipocytes of women with PCOS [20], a defect that was not, however, confirmed by Ciaraldi et al [13]. Moreover, Lystedt et al found a normal insulin dose-response curve along with diminished maximal insulin-stimulated glucose transport in subcutaneous adipocytes of obese PCOS women [21]. Ciaraldi et al also showed decreased maximal insulin-stimulated autophosphorylation with no apparent defect in receptor kinase activity [13].…”
Section: Peripheral Tissuesmentioning
confidence: 98%
“…The differentiated adipocytes display phenotypic characteristics of genuine adipocytes, that is, freshly isolated ones. Specially, they respond to physiologically relevant concentrations of hormones, including insulin and β-adrenergic agonists (Fried et al, 2010; Lee & Fried, 2012; Lee, Wu, & Fried, 2012; Lystedt et al, 2005; Zierath et al, 1998). Further, ASCs are also useful for assessing donor- and origin-dependent effects (depot, sex, age, obesity, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Although several human adipose cell lines are available, including Simpson‐Golabi‐Behmel syndrome (SGBS) and Human multipotent adipose‐derived (hMAD) , primary preadipocytes isolated from adipose tissues can be differentiated into adipocytes in vitro and are useful for studies of donor or depot‐dependent effects . In addition, newly differentiated human adipocytes in culture respond to physiologically relevant concentrations of hormones, insulin, and beta‐adrenergic agonists . Thus, primary cultures of human preadipocytes and adipocytes are valuable tools for the studies of adipocyte development and function and their use is expected to increase.…”
Section: Introductionmentioning
confidence: 99%